ICOS/ICOSLG and PD-1 Co-Expression is Associated with the Progression of Colorectal Precancerous- Carcinoma Immune Microenvironment - Zhang Y; Wang XL; Liu JJ; Qian ZY; Pan ZY; Song NP; Chen HY; Zhang W; Zhang X (Dove Medical Press, 2023)
Yu Zhang,1,* Xue-Li Wang,2,* Jing-Jing Liu,3 Zhen-Yuan Qian,4 Zheng-Yang Pan,5 Ni-Ping Song,5 Hui-Yan Chen,6 Wei Zhang,7 Xin Zhang8 1Cancer Center, Department of Gastroenterology, Zhejiang Provincial People's Hospital (Affiliated People's Hospital, Hangzhou Medical College), Hangzhou, Zhejiang, People's Republic of China; 2College of Pharmaceutical Science, Zhejiang University of Technology, Hangzhou, Zhejiang, People's Republic of China; 3Bengbu Medical College, Bengbu, Anhui, People's Republic of China; 4General Surgery, Cancer Center, Department of Gastrointestinal and Pancreatic Surgery, Zhejiang Provincial People's Hospital (Affiliated People's Hospital, Hangzhou Medical College), Hangzhou, Zhejiang, People's Republic of China; 5The Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 6Clinical Laboratory, Tongxiang First People's Hospital, Tongxiang, Zhejiang, People's Republic of China; 7Department of Gastrointestinal Surgery, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 8Cancer Center, Department of Pathology, Zhejiang Provincial People's Hospital (Affiliated People's Hospital, Hangzhou Medical College), Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhang, Cancer Center, Department of Pathology, Zhejiang Provincial People's Hospital (Affiliated People's Hospital, Hangzhou Medical College), No. 158 Shangtang Road, Hangzhou, Hangzhou, Zhejiang, 310014, People's Republic of China, Tel +86 13758197690, Fax +86 057185893288, Email zhangxin120189@163.com Wei Zhang, Department of Gastrointestinal surgery, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People's Republic of China, Email zhangweils1968@163.comPurpose: This study aimed to investigate the expression of inducible T-cell co-stimulator (ICOS) and its ligand (ICOSLG), along with their association with clinicopathological features and influence on the immune profile in colorectal cancer (CRC).Patients and Methods: The Cancer Genome Atlas Colorectal Adenocarcinoma cohorts were used. We also analyzed 131 clinical samples of colon lesions, including precancerous lesions (hyperplastic polyps, low-grade dysplasia, and high-grade dysplasia) and CRC tissues. We conducted immunohistochemical (IHC) assays and multiple IHC (mIHC) of CD4+, Foxp3+ tumor-infiltrating lymphocytes (TILs), and PD-1/PD-L1 immune checkpoints in precancerous lesions and CRC samples from our patient subsets to determine changes and correlations in ICOS and ICOSLG expression during progression through the adenoma-carcinoma pathway.Results: High expression of ICOS and ICOSLG was a significant factor in CRC in multiple analyses and was positively correlated with CD4+/Foxp3+ TIL density and PD-1/PD-L1 expression, which increased with the sequential progression of lesions from precancerous tissues to carcinoma. Multivariable logistic regression analysis suggested that the location and expression level of ICOS/ICOSLG may be involved in precancerous-carcinoma progression. The co-expression status of PD-1 and ICOS/ ICOSLG could stratify patients with colorectal lesions into three groups of low, moderate, and high risk of progression. According to this classification and mIHC assays, we found a strong correlation between increased PD-1+ICOS+ or PD-1+ICOSLG+ co-expression and CRC, which might be deemed an independent factor in carcinogenesis.Conclusion: Increased ICOS/ICOSLG expression may be associated with the progressive formation of Foxp3+ TILs in the immune microenvironment and may further promote the development of the abnormal cytology of colorectal lesions from precancerous neoplasia to CRC. Our findings support the interpretation that enhanced co-expression of PD-1+ICOS+ or PD-1+ICOSLG+ contributes to the immune-active microenvironment of the colorectal adenoma-carcinoma sequence.Keywords: precancerous-carcinoma, immune environment, ICOS/ICOSLG, PD-1/PD-L1, tumor-infiltrating lymphocytes